2010
DOI: 10.1590/s1413-70542010000500010
|View full text |Cite
|
Sign up to set email alerts
|

Fitoseídeos (Acari: Phytoseiidae) associados a cafezais e fragmentos florestais vizinhos

Abstract: RESUMOExistem poucas informações sobre a fauna de ácaros predadores (Phytoseiidae) em ambientes naturais brasileiros adjacentes a agroecossistemas cafeeiros (Coffea spp.) ou sobre a influência que essa vegetação exerce como reservatório de ácaros predadores. Neste estudo, objetivou-se avaliar a diversidade destes organismos em cafeeiros e fragmentos florestais adjacentes. ABSTRACTThere is little information about the fauna of predatory mites (Phytoseiidae) in Brazilian natural environments, adjacent to coffee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
2
9
0
1
Order By: Relevance
“…E. concordis foi encontrada em estudos de diversidade em Euforbiáceas e considerada uma espécie muito abundante em estudos de levantamento em espécies florestais CASTRO e MORAES, 2010). A espécie de ácaro predador I. zulugai é relatada em constante associação com fitófagos em seringueira (Hevea brasiliensis), cafeeiro (Coffea arábica) e erva-mate (Ilex paraguariensis) (BELLINI et al, 2008;SILVA et al, 2010;GOUVEA et al, 2006). A espécie A. largoensis tem sido muito estudada como regulador de população de ácaros fitofágos, principalmente em palmeiras (CARRILO, 2011;CARRILO, 2014).…”
Section: Methodsunclassified
“…E. concordis foi encontrada em estudos de diversidade em Euforbiáceas e considerada uma espécie muito abundante em estudos de levantamento em espécies florestais CASTRO e MORAES, 2010). A espécie de ácaro predador I. zulugai é relatada em constante associação com fitófagos em seringueira (Hevea brasiliensis), cafeeiro (Coffea arábica) e erva-mate (Ilex paraguariensis) (BELLINI et al, 2008;SILVA et al, 2010;GOUVEA et al, 2006). A espécie A. largoensis tem sido muito estudada como regulador de população de ácaros fitofágos, principalmente em palmeiras (CARRILO, 2011;CARRILO, 2014).…”
Section: Methodsunclassified
“…Feres (2005, 2008) reported occurrence of E. citrifolius, E. concordis and I. zuluagai in cultivations of rubber-trees, as well as in native areas close to the plantations. Silva et al (2010) and Berton (2009) also verified occurrence of those three phytoseiids species in coffee crops neighboring forest fragments in the south of Minas Gerais State and neighboring a forest fragment in the city of Monte Alegre do Sul, São Paulo State, respectively. Albuquerque (2006) registered E. concordis and I. zuluagai in orange crops and in the neighboring vegetation, in the city of Jaguariúna, São Paulo State.…”
Section: Discussionmentioning
confidence: 90%
“…In Brazil, some surveys have already been developed to analyse influence of the neighboring vegetation on occurrence of mite in cultivation of rubber-tree Feres, 2005, 2008), orange (Albuquerque, 2006) and coffee (Silva et al, 2010;Berton 2009). Demite and Feres (2007) also studied the relevance of native areas as reservoirs for Hirsutella thompsonii, an entomopathogenic fungus registered attacking the phytophagous mites more abundant in cultivation of rubber-tree crop in Mato Grosso State.…”
Section: Introductionmentioning
confidence: 99%
“…A. operculatus was observed only in the forest area. Silva et al (2010) also reported that the mites common in agroecosystems such as coffee plantations and in the surrounding native vegetation indicate that the natural environments are hosts to predatory mites that likely spontaneously migrate to these agroecosystems and help naturally control pest mites. In the present study, species common to both ecosystems (sugarcane crops and caboatã trees in the Atlantic forest) were also observed.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the predatory mites found in the present study belonging to these genera are predators of mites of the Eriophyidae, predominant family on both sugarcane and C. oblongifolia. Silva et al (2010) reported the occurrence of T. mangleae associated with coffee plantations and of A. operculatus associated with coffee plantations and with the natural vegetation in the forest fragments surrounding the crops in the state of Minas Gerais. In the present study, T. mangleae was observed in the sugarcane area as well as in the Atlantic forest fragment.…”
Section: Resultsmentioning
confidence: 99%